A comprehensive review and update on the non-biologic treatment of adult noninfectious uveitis: part I. (October 2014) - Lee, Kyungmin; Bajwa, Asima; Freitas-Neto, Clovis A; Metzinger, Jamie Lynne; Wentworth, Bailey A; Foster, C Stephen
<x xml:space="preserve">Abstract</x> Introduction: Treatment of adult, noninfectious uveitis remains a challenge for ophthalmologists around the world. The disease accounts for almost 10% of preventable blindness in the US and can be idiopathic or associated with infectious and systemic disorders. Strong evidence is still emerging to indicate that pharmacologic strategies presently used in rheumatologic or autoimmune disease may be translated to the treatment of intraocular inflammation. Corticosteroid monotherapy is widely regarded as wholly inappropriate, due to the unfavorable risk/benefit profile and poor long-term outcomes. Treatment plans have shifted away from low-dose, chronic corticosteroid therapy for maintenance, towards medium- to high-dose therapy for acute inflammation, followed immediately by initiation of immunomodulatory therapy. These therapies follow the 'stepladder approach', whereby least to more aggressive therapies are trialed to induce remission of inflammation, eventually without corticosteroids of any form (topical, local and systemic). Areas covered: This two-part review gives a comprehensive overview of the existing medical treatment options for patients with adult, noninfectious uveitis, as well as important advances for the treatment of ocular inflammation. Part I covers classic immunomodulation and latest information on corticosteroid therapy. Expert opinion: The hazard of chronic corticosteroid use for the treatment of adult, noninfectious uveitis is well-documented. Corticosteroid-sparing therapies, which offer a very favorable risk–benefit profile when administered properly, should be substituted.